2020
DOI: 10.1515/pthp-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Removal of bacterial growth inhibition of anticancer drugs by using complexation materials

Abstract: In the context of batch production of cytotoxic drugs in hospital pharmacies with the need of sterility testing, the objective was to validate the use of Rapid Microbiological Method (RMM), and to develop adequate neutralization method in case of inhibition of bacterial growth. The potential microbiological growth inhibitory effect of three anticancer drugs (5 fluorouracil, irinotecan and oxaliplatin) selected for batch production was assessed on BacT/ALERT® system. Among cytotoxic drugs, only 5FU exhibited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Research by Kim et al (2000) showed that the anthracycline antibiotic Da2B at concentrations in the range of 7.5-10 µg/mL inhibited the growth of yeast Saccharomyces cerevisiae and Bacillus subtilis bacteria [56]. Other anticancer drugs (5-fluorouracil, irinotecan and oxaliplatin) are characterized by their antimicrobial activity against B. subtilis [57]. The research carried out in this study shows that during the biodegradation of anthracycline antibiotics by immobilized mycelium of B. adusta CCBAS 930, no toxic compounds for plants or microorganisms are formed.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Kim et al (2000) showed that the anthracycline antibiotic Da2B at concentrations in the range of 7.5-10 µg/mL inhibited the growth of yeast Saccharomyces cerevisiae and Bacillus subtilis bacteria [56]. Other anticancer drugs (5-fluorouracil, irinotecan and oxaliplatin) are characterized by their antimicrobial activity against B. subtilis [57]. The research carried out in this study shows that during the biodegradation of anthracycline antibiotics by immobilized mycelium of B. adusta CCBAS 930, no toxic compounds for plants or microorganisms are formed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies regarding the potential of microbial growth in cytotoxic and non-cytotoxic RTA parenteral preparations have been published. 4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Viability tests are missing for numerous recently licensed monoclonal antibodies (mAb), filgrastim, and few small molecules introduced in anti-cancer therapy in recent years. The aim of this viability study was to investigate the potential growth promoting nature of 20 RTA parenteral preparations used for SACT.…”
Section: Introductionmentioning
confidence: 99%